Descrição de duas novas técnicas cirúrgicas para o tratamento de prolapso vaginal em vacas zebuínas: Vaginectomia parcial e vaginopexia dorsal - Hellú, José Abdo de Andrade [UNESP] (FapUNIFESP (SciELO), 2015)
Vaginal prolapse is an increasing problem in non-pregnant zebuine cows that so far conventional surgical techniques such as Caslick, Buhner and Flessa have failed to replace. This study aimed to assess the use of two new techniques, partial vaginectomy and dorsal vaginopexy, for the replacement of the prolapsed vagina in 812 adult zebuine cows (nelore, gir and brahman breeds) from several farms during a four years period. The selection of the technique to be used was based on clinical history, physical examination and stage of the vaginal prolapse. Post-surgical results indicated a high recovery percentage for partial vaginectomy and dorsal vaginopexy (93.4% and 96.1%, respectively), low relapse rate (6.3% and 3.7%, respectively) and low mortality (between 0.2% and 0.3%, respectively). Altogether, these findings showed that both techniques can be used for the effective reduction of vaginal prolapse in non-pregnant zebuine cows.
Description of two new surgical techniques for the treatment of vaginal prolapse in zebuine cows: Partial vaginectomy and dorsal vaginopexy
Keywords: Cow; Prolapse; Vaginectomy; Vaginopexy and vaginal